Unusual Location of Residual Mass in an Uncorrected Undescended Testis with Germ Cell Tumor - Navid Masoumi; Mostafa Farajpour; Atoosa Gharib (Case Reports in Urology)
Intra-abdominal cancer in an adult with undescended testis (UDT) is rare owing to widespread screening and management during childhood. Here, we present a 33-year-old gentleman with a complaint of abdominal pain and pelvic mass which appeared to be an uncorrected UDT with cancerous degeneration. Additional evaluation revealed a suspicious mass in the retrovesical space which remained after chemotherapy. Histologic evaluation after resection of this mass indicated cancer spread of testicular origin behind the bladder.